Sensory Processing in the Dorsolateral Striatum: The Contribution of Thalamostriatal Pathways - Alloway, Kevin D.; Smith, Jared B.; Mowery, Todd M.; Watson, Glenn D. R. (Frontiers in Systems Neuroscience, 2017)
The dorsal striatum has two functionally-defined subdivisions: a dorsomedial (DMS) region involved in mediating goal-directed behaviors that require conscious effort, and a dorsolateral (DLS) region involved in the execution of habitual behaviors in a familiar sensory context. Consistent with its presumed role in forming stimulus-response (S-R) associations, neurons in DLS receive massive inputs from sensorimotor cortex and are responsive to both active and passive sensory stimulation. While several studies have established that corticostriatal inputs contribute to the stimulus-induced responses observed in the DLS, there is growing awareness that the thalamus has a significant role in conveying sensory-related information to DLS and other parts of the striatum. The thalamostriatal projections to DLS originate mainly from the caudal intralaminar region, which contains the parafascicular (Pf) nucleus, and from higher-order thalamic nuclei such as the medial part of the posterior (POm) nucleus. Based on recent findings, we hypothesize that the thalamostriatal projections from these two regions exert opposing influences on the expression of behavioral habits. This article reviews the subcortical circuits that regulate the transmission of sensory information through these thalamostriatal projection systems, and describes the evidence that indicates these circuits could be manipulated to ameliorate the symptoms of Parkinson's disease and related neurological disorders.